Weather based pest forewarning models for mealybug infestation in Robusta coffee (Coffea canephora) - M. Jayakumar; M. Rajavel (Journal of Agrometeorology, 2019)
An investigation was carried out to study the effect of weather parameters on mealybug infestation in Robusta coffee and to develop forewarning model using 39 years (1977 to 2015) pest data on mealy bug damage in coffee plantations collected at Regional Coffee Research Station, Chundale, Wayanad district of Kerala were recorded at fortnightly intervals during 1977 to 2015 (39 years). The results revealed that mealybug infestation was found to vary with season and also year to year. Fruit setting and budding stages of coffee were severely damaged by mealy bug. Analysis indicated that annually, average damage due to mealy bug was 6.4 per cent and ranged between 5.4 per cent in 1984 to 9.7 per cent in 2011. The mealybug damage was maximum during summer season and lowest during South-West Monsoon (June-September) season. Season wise regression models were developed using data up to 2013 for forewarning per cent damage of mealy bug and validated for 2014 and 2015. The model for summer season mealybug damage has maximum R2=0.79 which can be used for operational forecasting of mealy bug damage.